Lightweight detection system of shared spam attacks - Shao-qing LV; Dan FAN; Yu-qing ZHANG (Tongxin xuebao)
Spam is one of the most serious attacks against online social networks (OSN).Recently a new type of spam attack occurs,which named shared spam attack.The shared spam attack can separate the storage and dissemination of spam content,making the existing detection systems no longer effective.To address this problem,an empirical analysis of the process and properties of this new spam attack is performed.A novel lightweight iterative detection algorithm (LIDA) is proposed to detect spam accounts in OSN with these properties.LIDA contains two steps:target filter and content detection.It also noteworthy that LIDA is a lightweight algorithm to infer more spam accounts by exploiting spam accounts’ sharing instead of scanning or analyzing all accounts.Experimental results in RenRen,which has successfully detected 9 568 spam accounts,30 732 spam albums and 2 626 780 spam URL in four round iterations,indicate that LIDA is effective and efficiency in detecting shared spam accounts.